Comparison of copper rotor bars with aluminium rotor bars using FEM software - A performance evaluation - Ismail, Daut, Prof. Dr.; Anayet, Karim; Gomesh Nair, Shasidharan; Asri, M.; Mohd Irwan, Yusoff (Institute of Electrical and Electronics Engineering (IEEE), 2010)
Link to publisher's homepage at http://ieeexplore.ieee.org/